Utilization of Interactive Booklets on World War II History Material in Realizing P5 Values for Class XI Students at SMAN 14 Semarang - Shafa Audilla Rahmawati; Syaiful Amin (Historia, 2026)
This study aims to describe the use of interactive booklets in history learning, especially World War II material and its role in realizing the values of the Pancasila Student Profile (P5) in class XI students of SMAN 14 Semarang. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The study results indicate that using interactive booklets can significantly improve students' understanding of history material. In addition, it also encourages the growth of P5 values in students. This can be seen from the active participation of students in the interview session discussion and their ability to respond to the values of humanity and peace. Thus, interactive booklets are an effective and relevant learning media in supporting the implementation of the Merdeka Curriculum.